2019
DOI: 10.1097/md.0000000000015498
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-based network analyses and candidate genes associated with Kashin-Beck disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…GO enrichment analysis demonstrated that the DMGs and DEGs are mainly enriched in biological processes, for instance, regulation of transforming growth factor beta activation, response to growth factor, extracellular matrix organization, positive regulation of cell death and apoptotic signaling pathway. These findings are consistent with the results of the previous studies [ 21 23 ]. Guo et al found the expression of transforming growth factor beta was significantly altered in KBD cartilage, suggesting the association of transforming growth factor beta with cartilage repair [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…GO enrichment analysis demonstrated that the DMGs and DEGs are mainly enriched in biological processes, for instance, regulation of transforming growth factor beta activation, response to growth factor, extracellular matrix organization, positive regulation of cell death and apoptotic signaling pathway. These findings are consistent with the results of the previous studies [ 21 23 ]. Guo et al found the expression of transforming growth factor beta was significantly altered in KBD cartilage, suggesting the association of transforming growth factor beta with cartilage repair [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…Guo et al found the expression of transforming growth factor beta was significantly altered in KBD cartilage, suggesting the association of transforming growth factor beta with cartilage repair [ 21 ]. Besides, previous studies have shown the KBD-related genes and deoxynivalenol-regulated genes enriched in the cellular response to growth factor stimulus and extracellular matrix organization respectively [ 22 , 23 ]. It is well recognized that apoptosis of chondrocytes plays a vital role in the pathogenesis of KBD.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes associated with CMT were collected by retrieving the human genetic association studies deposited in PUBMED ( http://www.ncbi.nlm.nih.gov/pubmed/ ). Referring to published studies [ 17 19 ], we searched for reports related to CMT with the term (Charcot-Marie-Tooth Disease [MeSH]) and (polymorphism [MeSH] or genotype [MeSH] or alleles [MeSH]) not (neoplasms [MeSH]). Up to 10 November 2019, a total of 674 publications were retrieved for the disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, we visualized the PPI network by means of Cytoscape software (version 3.7.1). Furthermore, the Molecular Complex Detection (MCODE) [ 17 , 31 , 32 ] in Cytoscape software was then performed to select appropriate modules of the PPI network to identify the most important MCODE clusters according to clustering scores. The detailed options set as degree cutoff = 2, K-core = 2, node score cutoff = 0.2, and MAX depth = 100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation